Biosecurity for the Poultry Industry - Gary Butcher; Mojtaba Yegani (EDIS, 2009)
VM-176, a 5-page illustrated fact sheet by Gary Butcher and Mojtaba Yegani, describes issues surrounding biosecurity for poultry operations, and important considerations for designing a comprehensive biosecurity program. Published by the UF College of Veterinary Medicine, Large Animal Clinical Sciences Department, January 2009.